Corruption, Policing and Migration: Exploring the Interaction Between Migrant Workers and Police in Russia, Ukraine and the UK - Markovska, A.; Марковська, Г. О.; Serdiuk, O. O.; Сердюк, О. О.; Sokurenko, V. V.; Сокуренко, В. В.; Valerii Sokurenko (International Migration. - 2018. - Vol. 57 (1). - P. 145-162, 2018)
Розглянуто права трудящих-мігрантів та досвід країн, що їх приймають. На основі даних інтерв'ю, проведених з трудовими мігрантами у Великобританії, Росії та Україні, вивчено їхні стосунки з поліцією в країнах, що приймають. Підкреслено,що досвід поліції у країнах, що приймають, може дати важливе розуміння практичних аспектів діяльності поліції, який не слід розглядати окремо від контексту етнічного походження трудових мігрантів.

The rights of migrant workers and their experiences in host countries have been high on the political agendas of Europe and beyond. This article uses data from 138 semi‐structured interviews conducted with migrant workers in the UK, Russia and Ukraine to study their relationships with the police in host countries. We aim to contribute to the literature on policing and migration by analysing three different host countries, and the experience of temporary migrant workers regarding policing within each country. We suggest that the interplay between the experiences of policing in home and host countries can provide important insights into the practicalities of policing, but should not be considered apart from the context of the ethnic origin of migrant workers.

Рассмотрены права трудящихся-мигрантов и опыт стран, которые их принимают. На основе данных интервью, проведенных с трудовыми мигрантами в Великобритании, России и Украине, изучено их отношения с полицией в принимающих странах. Подчеркнута важность опыта полиции в данных странах: он может дать важное понимание практических аспектов деятельности полиции, и в тоже время его не следует рассматривать в отрыве от контекста этнического происхождения трудовых мигрантов.
Keywords: Державне адміністративне управління. Адміністративна діяльність. State Administration. Administrative Activity. Государственное административное управление. Административная деятельность; Соціологія. Соціальна робота. Sociology. Social Work. Социология. Социальная работа; Наукові публікації. Scientific publications. Научные публикации; publikatsii u zarubizhnomu vydanni; publikatsii u WoS; publikatsii u Scopus; зарубіжний досвід; зарубежный опыт; foreign experience; миграция; міграція; migration; migrant workers; трудові мігранти; рабочие мигранты; Великобританія; Великобритания; United Kingdom; Росія; Россия; Україна. Ukraine. Украина; Ukraine; interviews; интервью; інтерв'ю; поліція; полиция; police; відносини з поліцією; отношения с полицией; relations with the police